Composite action of hexagonal concrete-filled steel tubular stub columns under axial loading. (October 2016) - Ding, Fa-xing; Li, Zhe; Cheng, Shanshan; Yu, Zhi-wu
Abstract: Four groups of axial compression tests on hexagonal CFT stub columns have been carried out aiming to investigate the effects of the concrete strength and steel ratio on the behaviour of hexagonal CFT stub columns. Studies on parametric analysis and composite action between core concrete and steel tube have been carried out using FE modelling which had been benchmarked using the test data. Based on the essential data obtained in this paper, the ratio of axial stress-yield strength of steel tube was determined at the ultimate state. The stress contour of core concrete was simplified to an unconfined area without constraint and a confined area with uniform constraint imposed by hexagonal steel tube. Eventually, a practical design equation of the ultimate bearing capacity of hexagonal CFT stub columns was proposed based on the superposition principle. An excellent agreement between the proposed equation and the experimental results was observed, with an average ratio of predicted to measured capacity of 1.08 and a standard deviation of 0.05. Highlights: Mechanical behaviour on hexagon CFT stub columns were tested. A 3D FE model is developed to carry out parametric studies. Effects of the concrete strength and steel ratio have been studied. A practical formula on axial resistance of hexagon CFT stub columns was proposed.